PROBLEMS AND SOLUTIONS IN THE INTEGRATION OF TAX AND FINANCIAL ACCOUNTING SYSTEMS - Bakirov Norbek Norquchqor o’g’li (Modern American Journals, 2025)
This article analyzes the issues of integrating tax and accounting systems in the context of the digital economy. The main objective of the research is to improve management efficiency by automating the exchange of information between tax and accounting data. The research object is the integration process of information systems between tax authorities and business entities. Methodologically, the study applies system analysis, SWOT evaluation, comparative analysis, and economic-mathematical modeling methods. Based on the results of the analysis, a conceptual model for determining the Integration Efficiency Index (ESI) has been developed. Drawing on international experience (Estonia, South Korea, and Singapore), the obtained results allowed the development of practical recommendations to enhance the coherence of information systems in the context of Uzbekistan. The scientific novelty of the research lies in the development of a conceptual model for quantitatively assessing the economic efficiency of tax and accounting system integration, adapted to Uzbekistan’s economic practice. The proposed approach serves as a methodological basis for further deepening the digital transformation of tax administration and the financial reporting system.
Keywords: Digital economy, tax system, accounting, information system integration, economic efficiency, data exchange, digital transformation, tax administration.